Characterization of local chicken production and management systems in Babati, Tanzania - Marwa, L.; Lukuyu, Ben A.; Mbaga, S. (International Livestock Research Institute, 2016)
The study was done to generate fundamental information for the improved nutritional management in rural chicken production in Tanzania. A survey was conducted aimed at defining the socioeconomic characteristics of the rural chicken production environments in Babati district in Tanzania. The survey included both individual interviews and participatory group discussions. A total of 141 households from four different wards were interviewed. The questionnaire was designed to collect data covering general information on rural chicken production such as socio-management characteristics, production status and population structure. The findings showed that 96.5% of the chickens kept in Babati district are local strains and they are mostly owned by women. Production of meat and eggs for home consumption is the primary function of chickens in the surveyed areas followed by the sales of both eggs and live birds as source of income. The mean chicken flocksize per household was 5. Most of the village households (53.2%) were keeping their chickens under scavenging feeding system. The chickens were left to search for their feeds with rare supplementations of handful unbalanced feeds comprised of either maize bran, sorghum or sunflower seed cake. Kitchen left-overs were found to be the dominant supplement throughout the year. Other systems were the semi-scavenging and confinement with fully indoor feeding systems, which were also found to face unbalanced feeding challenge. The sector is then dominated with scavenging nutritional management, absence of vaccination programs and high risk of exposure of chickens to disease and predators. Ultimately, the production system in all geographic sites studied revealed similar characteristics of high mortality rate (60%) mainly due to malnutrition, diseases, predators and rough environmental conditions such as rainfall. The hens were found producing an average of 13 eggs per clutch with only 3 clutches per year. Price of chickens at village level was also found to fluctuate over the year mainly due to disease incidences and festival seasons such as Christmas and Easter. The results draw a need for interventions in improved strategies on nutritional management of the scavenging chickens to enhance indigenous chicken productivity improvement.